HUBUNGAN PROKRASTINASI, SOCIAL SUPPORT, DAN SELF EFFICACY DENGAN MINAT BERWIRAUSAHA SISWA - Arianto Lubis; Wanapri Pangaribuan (Universitas Negeri Medan, 2022)
AbstractThis study aims to determine the relationship: 1) Procrastination, Social Support, and Self Efficacy with Interest in Entrepreneurship, 2) Procrastination with Interest in Entrepreneurship, 3) Social Support with Interest in Entrepreneurship, 4) Self Efficacy with Interest in Entrepreneurship. This research is a quantitative research, the population in this study are students of SMK Negeri 1 Percut Sei Tuan. The sampling technique used is purposive sampling with a total sample of 92 students. The data collection technique is in the form of a questionnaire. The data analysis technique used is multiple linear regression analysis, hypothesis testing, analysis prerequisite test. The results showed that: 1) There was a negative relationship between procrastination and interest in entrepreneurship. 2) There is a positive and significant relationship between social support and interest in entrepreneurship. 3) There is a positive and significant relationship between self-efficacy and interest in entrepreneurship. 4) There is a joint relationship between procrastination, social support and self-efficacy with interest in entrepreneurshipKeywords: procrastination, social support, self efficacy, enterpreneurship AbstrakPenelitian ini bertujuan untuk mengetahui hubungan : 1) Prokrastinasi, Social Support, Dan Self Efficacy Dengan Minat Berwirausaha, 2) Prokrastinasi dengan Minat Berwirausaha, 3) Social Support dengan Minat Berwirausaha, 4) Self Efficacy dengan Minat Berwirausaha. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasi, populasi dalam penelitian ini adalah siswa SMK Negeri 1 Percut Sei tuan. Teknik sampling yang digunakan adalah purposive sampling dengan jumlah sampel sebanyak 92 siswa. Teknik pengumpulan data menggunakan angket. Teknik analisis data yang digunakan adalah analisis regresi linier ganda, pengujian hipotesis, uji prasyarat analisis. Hasil penelitian menunjukkan bahwa : 1) Terdapat hubungan negatif antara prokrastinasi dengan minat berwirausaha. 2) Terdapat hubungan positif dan signifikan antara social support dengan minat berwirausaha. 3) Terdapat hubungan positif dan signifikan antara self efficacy dengan minat berwirausaha. 4) Terdapat hubungan bersama-sama prokrastinasi, social support dan self efficacy dengan minat berwirausaha.Kata Kunci: Prokrastinasi, Social Support, Self Efficacy, Minat Berwirausaha